Therapeutic effects of music, dance, arts and play to children with special needs, Silahis Centers Division of City Schools Manila Academic Year 2006-2007 : a study - Blanco, Ma. Cristala C. (Manila : National University, 2007)
This study revolved around the assessment of the SPED teacher respondents on the therapeutic effects of music, dance, arts and play to the children with special needs during the academic year 2006-2007.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- List of Figures -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Descriptive Design.
Includes bibliographical references.